Knowledge recombination along the technology life cycle - Martin Kalthaus (Journal of Evolutionary Economics, 2020)
This study sheds light on how recombination of different kinds of knowledge changes along the technology life cycle. From a theoretical point of view, the cyclical technology life cycle model is extended to account for the influence of recombination of different kinds of knowledge in the different life cycle phases. This model is empirically tested for the technological life cycle of wind power and photovoltaics in Germany for the period from 1970 until 2006. Patent forward citations are considered as recombinatorial success and inventors' patenting experience proxy different kinds of knowledge. Negative binomial regressions as well as rolling-window regressions are used to estimate the relevance of different kinds of knowledge along the technology life cycle. Results reveal that different kinds of knowledge matter along the technology life cycle. In the era of ferment, knowledge from domains external to the technology is relevant, but for the dominant design and the era of incremental change, new and specialized knowledge is most important. However, there are technological differences and deviations from the model. Rolling-window regressions reveal nuanced changes in the life cycle phases. The results have several policy and management implications, especially for the timing of whom to fund or hire for inventive activity.
Keywords: O31; O34; Q55; 330; Technology life cycle; Knowledge recombination; Wind power; Photovoltaics; Patent data; Rolling-window regression